A Revised Code of Ordinances of the City of Tuscaloosa 163, § 387 (1885) - (:unkn) unknown (My University, 1885)
Prohibited keeping more than twenty-five pounds of gun powder or other explosive. Also prohibited sale of gun powder by artificial light.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER